Kolektor surya jenis sirkular dengan memanfaatkan neon bekas sebagai kaca penutup - I Ketut Gede Wirawan (Jurnal Energi Dan Manufaktur, 2008)
To reduce the dependence to conventional energy resource, an effort to develop alternative energy application should be considered. One of them is the solar energy. Tubular solar thermal collector is a device to absorb the solar energy in from of thermal energy and transfer it into fluid. In water heating process, the solar collector which consists of some ex turbular lamp as cover glass, and finned absorber pipes, is designed and will be studied to obtain its performance. The mass flow rate amd inlet temperature of working fluid must be adjusted to achive the highest efficiency for a certain tubular solar collector.The experiment to examine the performance of the device done from 10.00 AM to 2.00 PM. The performance is representated by the rate changes of mass flow and inlet fluid temperature. The experiment shows that the best performance of this tubular solar collector is at mass flow rate of 250 cc/min with the maximum efficiency of 58.5 %